Diferenciação na venda de livros acadêmicos por meio de comércio eletrônico - Palladino, Cláudia Ferretto (2008)
The purpose of this work is to verify how sales of academic books are performed through Electronic Commerce in Brazil, investigating attributes which have to be considered to attract and retain customers. Simultaneously, it was identified practices of differentiation in strategic marketing and marketing programs applied in order to answer customer desires and to make their access easier. The starting point was previous studies made by others researchers who have detected as the most important attributes the ones related to functionality, design, content, offerings, reliability, usability, payments process and communication with the clients. It was used exploratory research as methodology, analyzing secondary data in three stages collecting the most important attributes used by on-line bookstores for customers attracting and retaining which were determined earlier, observation research of those attributes on six on-line bookstores previously selected and collecting of data on E-Commerce in Brazil. The main conclusions refer to few differentiations of the adopted practices among the evaluated web sites and that is possible to use more deeply the available technological resources to increase the gain of productivity at academic books sales through Electronic Commerce